Reestructuración orgánica y funcional en la compañía de Transporte San Francisco de Chillogallo S.A. - Pinzón Colmenares, Jenifer Alejandra (2023)
The research's objective was to raise a functional organic structure for the San Francisco de Chillogallo S.A Transport Company, thus theoretically basing the elements for the functional organic restructuring in an organization, highlighting the types of structures, organization charts, flow charts, a chain of command, centralization, and decentralization. The significance of a well-defined structure in delineating roles, optimizing communication, and streamlining decision-making was emphasized. The present research used a quantitative approach methodology, descriptive type, the information was gathered using a survey comprising 17 questions, the reliability of which was determined by Crombrach's Alpha of 0.7.; found the following results: 47.8% of employees lack written functions, and 4.3% were undecided. Likewise, a significant 73.9% supported the creation of a functions manual. Finally, we presented a comprehensive proposal for restructuring; this included the development of a process map to clarify internal functioning, a structural organization chart to establish clear hierarchies, and detailed descriptions of positions in the structure down to their internal and external responsibilities and connections. The proposal seeks to optimize the operation and efficiency and to promote transparency in the system of the organization. This study highlights the importance of a well-defined and functional organizational structure for the success and adaptability of Compañía de Transporte San Francisco de Chillogallo S.A. in the current environment.